Routing congestion in VLSI circuits estimation and optimization - Saxena Prashant; Sapatnekar Sachin S; Shelar Rupesh S (New York Springer-Verlag, 2007)
This book provides the reader with a complete understanding of the root causes of routing congestion in present-day and future VLSI circuits, available techniques for estimating and optimizing this congestion, and a critical analysis of the accuracy and
Keywords: Integrated circuits; Very large scale integration